Effect of marital satisfaction on self‐regulation efforts in couples: Value of heart rate variability measurements. Issue 4 (20th April 2020) - Constant, Emilie; Leuchtmann, Lorena; Christophe, Véronique; Bodenmann, Guy; Gabrielli, François; Ott, Laurent; Nandrino, Jean‐Louis
Abstract : This study explored self‐regulatory efforts during the viewing of couple interactions and their association with relationship satisfaction. High‐frequency heart rate variability (HF‐HRV) was measured for each participant during a video recall of a recent couple interaction to quantify the self‐regulatory processes governed by parasympathetic activity. Among 30 couples, HF‐HRV was measured continuously during three specific periods to explore its change over time using a video‐recall procedure: (1) resting state; (2) viewing of couple interactions (expressing daily life situations and conflictual interactions); and (3) recovery. Results of multilevel models revealed a u‐shaped pattern of HF‐HRV responses for men and women across the three periods with a nadir at the midway through the process. This pattern of physiological change (vagal suppression) reflects a flexible response to a stressful situation. Nevertheless, the pattern of physiological responses varied according to the level of relationship satisfaction. Men who were more satisfied in their couple relationship presented greater vagal suppression than dissatisfied men. In contrast, no significant HF‐HRV changes were found in women over the different periods of the video‐recall procedure and no moderating effect of relationship satisfaction. We discuss the different patterns of physiological responses observed both for men and women in terms of interindividual variability according to the level of their relationship satisfaction. The present study highlights the important role of relationship satisfaction in regulatory processes.